The Role of Supervisor Support on Work-Family Conflict and Employee Turnover Intentions in the Workplace with Mediating Effect of Affective Commitment in Twin Cities in the Banking Industry, Pakistan - Khan, Muhammad Iqbal; Shah, Syed Haider Ali; Haider, Aftab; Aziz, Shahab; Kazmi, Munaza (International Review of Management and Marketing, 2020)
Organizations compete in today’s world through its intangible assets which literature describe as human capital. Technology can be replaced but human capital cannot be replaced completely ever. Employee retention is center of attention for all the organizations’ nowadays. Retentions of employees’ mainly based on supervisors support and their affiliation with organization. This paper attempts to examine the impact of supervisor support on work family conflict and turnover intentions directly and indirectly through affective commitment. In order to collect the data this study used closed ended questionnaires from banking industry of twin cities of Pakistan. SEM (AMOS) was employed to test hypotheses. Findings reveal the mediating role of affective commitment particularly in context banking sector of Pakistan. This study filled the gap by investigating supervisor support on work family conflict along with affective commitment. Findings of this study are important from two perspectives. First is the banking sector and secondly the twin cities in which there is almost no study has been conducted before. Implications are particular for banking industry top managers and practitioners. Top management can implement such practices in order to retain their employees’. Keywords: Supervisor Support, Work-Family Conflict, Employee Turnover Intentions, SEM JEL Classifications: H15, M16 DOI: https://doi.org/10.32479/irmm.10807